An unusual case of dapsone syndrome - Mary Grace (Wolters Kluwer Medknow Publications, 2011)
Dapsone, a potent antiparasitic and anti-inflammatory compound, is mainly used in the treatment of leprosy and a variety of blistering skin diseases. It may cause a severe adverse drug reaction with multiorgan involvement known as dapsone hypersensitivity syndrome. We report an unusual case of dapsone hypersensitivity, manifesting as bone marrow suppression and peripheral pancytopenia in addition to fever, rash, and hepatosplenomegaly.